Monitoring of Debrecen WWTP Biogas Fermentation Processes by Chemical Methods - Truzsi, Alexandra; Bodnár, Ildikó; Fülöp, Zoltán (International Journal of Engineering and Management Sciences, 2017)
The anaerobic digestion is a widely used economical method for sewage sludge stabilization and also purification of waste water with a high organic content. All effective anaerobic digesters transform the organic matter into biogas containing methane, which usable component covers a significant share of the heat and electricity consumption of the wastewater treatment plant (WWTP). The increasing amount of biogas is a priority task of WWTPs, which we can achieve a deeper knowledge of anaerobic digestion processes. The main task of this study is the optimization of anaerobic sludge treatment of Debrecen WWTP. Digester towers processes and their impact on the biogas yield were also priority studied.